A new genus and species of damselfish (Pomacentridae) from the Eocene of Bolca, Northern Italy, with notes on the evolution of predator-prey interactions in coral reef fishes - Bellwood, David R.; Bannikov, Alexandre F.; Zorzin, Roberto (Zootaxa, 2025)
A new genus and species of damselfish †Chiarachromis salazzarii gen. et sp. nov. (Pomacentridae) from the Eocene (49 Ma) Pesciara deposits of the Bolca locality, Italy, is described. †Chiarachromis gen. nov. is characterized by a unique combination of vertebral (11+14=25) and unpaired fin-ray counts (D X, 11; A II, 7; C 7, I,7-6,I, 6), long pelvic fins, and the possession of three supraneurals. With exceptional preservation of the fin shape and the body form, this damselfish raises questions about the role of body shape, especially fin height, in the early evolution of reef fishes, and offers new insights into the rapid development of modern, predator-prey interactions in the early evolution of reef fishes.